The Dating of Heneni’s False Door at Hildesheim - Soleiman, Saleh.
This article deals with dating the false door of Heneni which was found at Giza and is now preserved in the Roemer-und Pelizaeus-Museum, Hildesheim. The false door is dated from late in the reign of Pepy II to the Eighth Dynasty on the basis of the place of its discovery in the cemetery, the name of its owner, the titles and epithets of the deceased, the prt-xrw formula, and its form and decoration. The small size and location of Heneni’s tomb are discussed. His rank and status are determined, the short offering formula on the false door is explicated, and a new reading and translation are suggested for the prt-xrw formula. doi: http://dx.doi.org/10.5913/jarce.56.2020.a013